2018
DOI: 10.3389/fpsyg.2018.00562
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Strategies of Affect Regulation and Their Associations With Subjective Well-Being

Abstract: Environmental strategies of affect regulation refer to the use of natural and urban socio-physical settings in the service of regulation. We investigated the perceived use and efficacy of environmental strategies for regulation of general affect and sadness, considering them in relation to other affect regulation strategies and to subjective well-being. Participants from Australia, Finland, Germany, Great Britain, Italy, India, the Netherlands, Portugal, and Sweden (N = 507) evaluated the frequency of use and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
56
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(58 citation statements)
references
References 71 publications
0
56
1
1
Order By: Relevance
“…The experience of these two distinct types of positive affect in nature is in line with research by . Recently, Korpela et al (2018) have noted that the role of nature in affect regulation is often overlooked. They show that there is a relationship between well-being and affect regulation.…”
Section: Discussionmentioning
confidence: 99%
“…The experience of these two distinct types of positive affect in nature is in line with research by . Recently, Korpela et al (2018) have noted that the role of nature in affect regulation is often overlooked. They show that there is a relationship between well-being and affect regulation.…”
Section: Discussionmentioning
confidence: 99%
“…It's clear that engagement with nature can induce positive emotions and this goes beyond restoration and counteracting negative affect (Kaplan and Kaplan 1989;Ulrich 1984). Nature also brings benefits when human 'selfcontrol' resources are not depleted (Beute and De Kort 2014), helping manage emotions (Richardson 2019); a role that is often overlooked (Korpela et al 2018). McMahan and Estes (2015) argue that the beneficial effects of nature on emotional well-being are driven primarily by increases in positive affect.…”
Section: Theories Relating Health/well-being To Naturementioning
confidence: 99%
“…A body of emotional regulation research evidences the links to well-being ( Gross, 2013 ; DeSteno et al, 2013 ). Korpela et al (2018) note how the role of nature in affect regulation is often overlooked and describe the relationship between affect regulation and well-being. Korpela et al (2018) call for further study into environmental affect regulation strategies.…”
Section: Introductionmentioning
confidence: 99%
“… Korpela et al (2018) note how the role of nature in affect regulation is often overlooked and describe the relationship between affect regulation and well-being. Korpela et al (2018) call for further study into environmental affect regulation strategies. Richardson et al (2016b) demonstrated how responses to nature exposure can be linked to affect regulation by considering the three-circle model of emotion ( Gilbert, 2009 ).…”
Section: Introductionmentioning
confidence: 99%